Chorioamnionitis and neonatal sepsis due to extended‐spectrum beta‐lactamase‐producing Escherichia coli infection: a case report - Saheed Akinola Shittu (Wiley, 2021)
Abstract Chorioamnionitis is an acute inflammation of the membranes and chorion of the placenta typically due to ascending polymicrobial infection in the setting of membrane rupture. It is a common complication of pregnancy associated with significant maternal, perinatal, and long‐term adverse outcomes. We present a case of placental infection leading to preterm delivery, severe neonatal sepsis, maternal wound infection, postnatal readmission, and prolonged hospital stay. This virulent infection was caused by multidrug–resistant extended‐spectrum beta‐lactamase (ESBL)‐producing Escherichia Coli (E. Coli), which represent a major worldwide threat according to the Centre for Disease Control and Prevention (CDC). It was managed with appropriate antibiotic therapy, patient‐centered approach, and multidisciplinary team involvement that led to favourable maternal and neonatal outcome.